Bio-Fermented Malic Acid Facilitates the Production of High-Quality Chicken via Enhancing Muscle Antioxidant Capacity of Broilers - Qiu, Kai; He, Weizhen; Zhang, Haijun; Wang, Jing; Qi, Guanghai; Guo, Naiwei; Zhang, Xin; Wu, Shugeng (Antioxidants, 2022)
Malic acid, an intermediate of the tricarboxylic acid (TCA) cycle, is a promising acidifier with strong antioxidant capacity. This study aimed to evaluate the effects of bio-fermented malic acid (BFMA) on promoting the body health, performance and meat quality of broilers. A total of 288 one-day-old Arbor Acres male broiler chicks were randomly divided into four treatments with six replicates in each. Every replicate had 12 chicks. Four experimental diets contained 0, 4, 8, and 12 g/kg BFMA, respectively. During the 42-day trial, mortality was recorded daily, feed intake and body weight of each replicate being recorded every week. Blood samples were collected on days 21 and 42 for chemical analysis. After slaughter at the age of 42 days, the carcass traits and meat quality of the broilers were measured, breast muscle samples were collected for the determination of antioxidant capacity, and cecal digesta were pretreated for microbiota analysis. Dietary BFMA significantly increased feed intake and daily gain, and decreased feed conversion ratio and death and culling ratio of the broilers at the earlier stage. The water-holding capacity of breast muscle indicated by the indexes of dripping loss and cooking loss was significantly increased by BFMA, especially at the addition level of 8 g/kg. Dietary BFMA significantly decreased the activity of superoxide dismutase and contents of immunoglobulin A and glutathione, and increased contents of immunoglobulin G and M in serum of the broilers. The contents of glutathione, inosinic acid, and total antioxidant capacity and the activities of glutathione-Px and superoxide dismutase were significantly increased by dietary BFMA, with the level of 8 g/kg best. The diversity of cecal microbiota of broilers was obviously altered by BFMA. In conclusion, as one of several acidifiers, addition of BFMA in diets could improve the performance and body health of broilers, probably by reinforcing immunity and perfecting cecal microbiota structure. As one of the intermediates of the TCA cycle, BFMA increases the water-holding capacity of breast muscle of broilers, probably through reducing lactate accumulates and enhancing antioxidant capacity.